Rolling Ball Media on the Writing Skills Rhyme for Fifth Grade Students of Elementary School - Sulrifka Tunnisa; Supartinah; Setiawan Edi Wibowo (Jurnal Ilmiah Sekolah Dasar, 2024)
In the world of education, creating a learning environment that inspires and motivates students is an important task of a teacher. One way that can be used to achieve this goal is by utilizing learning media. This research aims to analyze students' pantun writing skills in a study Pre-Eksperimental Design by design One Group Pretest-Posttest Design. This research process involves preparation, implementation and data analysis stages related to rhyme writing skills and student responses. The subjects of this research were 20 fifth grade students, who received special treatment using media Rolling Ball to measure the effectiveness of this media on the development of their pantun writing skills. The required data is collected through observation and tests. The results of data analysis using the methoddescriptive and inferential statistics. Pretest exam 0.07 and the posttest value of 0.28 is greater than the alpha value of 0.05, this shows that the pretest value and posttest data are normally distributed. The homogeneity test using the t test obtained a value of -8.529 with a 2-tailed sig of 0.000, greater than the alpha value of 0.05, so it can be concluded that there is a difference in the average pretest and posttest rhyme writing skills after using media treatment Roling Ball.